THE RECONSTRUCTION OF THE TEXTS IN ENGLISH BIOLOGY TEXTBOOK ENTITLED ANIMAL TAXONOMY - Gadis Herningtyasari (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2016)
This study aims to describe the errors are found in English Biology Textbook entitled Animal Taxonomy. By using Qualitative Descriptive method, this study classifies the errors based on Dulay, Burt, and Karshen (1982) method about Error Analysis, namely Omission, Addition, Misformation, and Misordering. From the results of the study, it was found that some categories of errors in which Omission Error is caused by the missing of items that need to complete the phrases or sentences. Then, addition error in which the addition of unnecessary items in the phrase or sentences. The next is Misformation refers to wrong form of words. The last is Misordering refers to incorrect placement of a morpheme or a group of morpheme. The errors are found in English Biology Textbook entitled Animal Taxonomy are caused by the different rules of grammar such as the construction of adjective and noun phrase, grammatical endings, the use of tenses, and the use of articles between two languages. From this output, it can be seen that Omission and Misordering are the dominant errors in English Biology Textbook entitled Animal Taxonomy. Therefore, it is necessary to reconstruct the text in English Biology Textbook entitled Animal Taxonomy to make it useable. Key words: Errors, English Biology Textbook, qualitative descriptive method.